2021
DOI: 10.3390/app11135821
|View full text |Cite
|
Sign up to set email alerts
|

Thrust Augmentation of Micro-Resistojets by Steady Micro-Jet Blowing into Planar Micro-Nozzle

Abstract: The present work investigates the impact of steady micro-jet blowing on the performance of a planar micro-nozzle designed for both liquid micro-thrusters and nitrogen cold-gas micro-resistojets. Two micro-injectors have been placed into the divergent region along the sidewalls, injecting a secondary flow of propellant perpendicularly to the wall where they have been located. The micro-jet actuator configuration is characterized by the dimensionless momentum coefficient cμ. The best performance improvement is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[2]. In the case of active controls, the researchers utilized a high-speed nozzle with an expanded duct and microjet controller; a small hole is drilled in the base region to control the flow, which was proven to be an efficient approach for the supersonic flow problem [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2]. In the case of active controls, the researchers utilized a high-speed nozzle with an expanded duct and microjet controller; a small hole is drilled in the base region to control the flow, which was proven to be an efficient approach for the supersonic flow problem [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that base pressure was controlled effectively through the employment of micro jets. Khan and Rathakrishnan [3] conducted experiments to modify base pressure. M = 1.87, 2.2, and 2.58, and NPR = 3, 5, 7, 9, and 11, were utilized as control parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation